In search of a modern character of a doctor: what examples to learn from the greats? Part II - Yu. V. Rodionova (Кардиоваскулярная терапия и профилактика, 2024)
The article continues the review of the development of medical knowledge in the context of the development of the image of a doctor in history in Russian and Russian medicine. Modern theories about the role of a doctor in the future are considered, which to some extent influence the formation of examples of images of doctors in professional education.